﻿Pilot Innovations Could Reignite Anemic Rural Finance - Kloeppinger-Todd, Renate (World Bank, 2012)
Rural finance and credit services to smallholder farmers are high-risk activities. But there is hope for a boost because rural finance has a pivotal role to play amid rising food prices and the need to increase agricultural production.